Experimental and numerical investigation of soil-foundation interface nonlinearity under dynamic loading - Koronides, Marios; Kontoe, Stavroula; Zdravković, Lidija; Vratsikidis, Athanasios; Pitilakis, Dimitris (My University, 2026)
Interface nonlinearity of shallow foundations has been found to significantly impact the dynamic response of soil-structure-interaction (SSI) systems; however, challenges remain in both its experimental and numerical characterisation. This study presents real scale free and forced vibration experiments, as well as three-dimensional nonlinear finite element analyses, to investigate the impact of interface nonlinearity, with particular emphasis on foundation rocking, on the response of an SSI system. The system comprises a steel frame structure, EUROPROTEAS, configured with either an 18 Mg or a 9 Mg structural mass and founded on a surface footing over soft soil. The study focuses on key parameters that influence interface nonlinearity, including structural weight, interface gaps, and static normal stresses that arise at the interface due to the structural self-weight and by densification from previous testing. Further development of an interface model is proposed which allows a more realistic simulation of the static stress distribution prior to the application of dynamic excitation. Both experimental and numerical data demonstrate the significant influence of interface nonlinearity on period lengthening and damping reduction, while also highlight a scenario where it can lead to a stiffer response. Additionally, the study emphasises the significant impact that the initial stress distribution can have on the response, demonstrating that a more uniform distribution can facilitate foundation rocking. Finally, it is demonstrated that a lighter structure can exhibit stronger interface nonlinearity than a heavier one, particularly when the external excitation is applied directly to the structure.
Keywords: Finite element analysis; Foundation rocking; Interface gaps; Real-scale experiments; Soil-foundation interface nonlinearity; Static interface stresses adjustment; Structural mass